The effect of occupational deregulation on wage premiums - Julia Bredtmann; Sebastian Otten; Timo Rammert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We analyze the impact of occupational deregulation on the wages of licensed workers. To do so, we exploit a deregulation policy in the German craft sector that removed the master certificate as a requirement for starting a business in about half of the craft occupations. Specifically, we examine the impact of this deregulation policy on the wage premium of incumbent master craftsmen. Our results indicate that the reform led to a 3% increase in the wage premium of masters in deregulated relative to regulated occupations. This effect is primarily driven by a substantial increase in the wages of masters in deregulated occupations. We attribute this increase to heightened competition for highly skilled workers in the affected occupations, stemming from a sharp decline in the number of craftsmen pursuing a master craftsmen degree after the reform. We further show that the increase in the wage premium of master craftsmen was particularly pronounced in East Germany, which experienced a large outflow of skilled workers after reunification. This general shortage of skilled labor, exacerbated by the increased scarcity of master craftsmen, is likely to have intensified competition for their expertise. – – In der vorliegenden Studie untersuchen wir die Auswirkungen beruflicher Deregulierung auf die Löhne von Beschäftigten. Als Untersuchungsgegenstand dient eine Reform der beruflichen Regulierung im deutschen Handwerk, durch die in etwa der Hälfte der Handwerksberufe der Meisterbrief als Voraussetzung für eine Unternehmensgründung abgeschafft wurde. Konkret untersuchen wir die Auswirkungen dieser Deregulierungspolitik auf die Lohnprämie von angestellten Handwerksmeistern. Unsere Ergebnisse zeigen, dass die Reform zu einem Anstieg der Lohnprämie von Meistern in deregulierten Berufen um 3% im Vergleich zu reglementierten Berufen geführt hat. Dieser Effekt ist vor allem auf einen deutlichen Anstieg der Löhne von Meistern in deregulierten Berufen zurückzuführen. Dieser Anstieg lässt sich durch den verschärften Wettbewerb um hochqualifizierte Arbeitskräfte in den betroffenen Berufen erklären, der auf den starken Rückgang der Zahl der Handwerker zurückzuführen ist, die nach der Reform einen Meistertitel erworben haben. Darüber hinaus zeigen wir, dass der Anstieg der Lohnprämie von Handwerksmeistern in Ostdeutschland, das nach der Wiedervereinigung eine starke Abwanderung von Fachkräften erlebte, besonders ausgeprägt war. Der durch die Reform verstärkte allgemeine Fachkräftemangel dürfte den Wettbewerb um hochqualifizierte Arbeitskräfte intensiviert und damit zu einem deutlichen Anstieg der Lohnprämie für Meister geführt haben.
Keywords: J24; J31; J44; L51; 330; Occupational licensing; deregulation; labor supply; wages